Effectiveness and safety of anti-PD-1 monotherapy or combination therapy in Chinese advanced gastric cancer: A real-world study - Li, Tao; Liu, Tingting; Zhao, Lei; Liu, Lu; Zheng, Xuan; Wang, Jinliang; Zhang, Fan; Hu, Yi (Frontiers in Oncology, 2023)
Purpose Gastric cancer (GC) is one of the most frequently diagnosed cancers and one of the leading causes of cancer deaths worldwide, especially in eastern Asia and China. Anti-PD-1 immune checkpoint inhibitors, Pembrolizumab and Nivolumab, have been approved for the treatment of locally advanced or metastatic gastric or gastroesophageal junction cancer (GC/GEJC). Our study evaluated the effectiveness and safety of anti-PD-1-based treatment (monotherapy or combination therapy) in Chinese patients with advanced or metastatic GC/GEJCs in a real-world setting. Methods A retrospective cohort study was conducted, and 54 patients from May 31, 2015, to May 31, 2021, were included in our analysis, including 19 patients treated with anti-PD-1 monotherapy and 35 patients treated with anti-PD-1 combination therapy. Demographic and clinical information were evaluated. Clinical response, survival outcomes, and safety profile were measured and analyzed. Results Overall, the median overall survival (mOS) was 11.10 months (95% CI, 7.05–15.15), and the median progression-free survival (mPFS) was 3.93 months (95% CI, 2.47–5.39). Of the patients, 16.7% achieved a clinical response, and 72.2% achieved disease control. Prolonged overall survival (OS) and progression-free survival (PFS) and increased clinical response were observed in the combination group compared with the monotherapy group, although statistical significance was not reached. In subgroups with live metastases or elevated baseline neutrophil-to-lymphocyte ratio (NLR) levels, combination therapy outperformed anti-PD-1 alone in survival outcomes. Patients treated with anti-PD-1 monotherapy (n = 5, 26.3%) had fewer treatment-related adverse events (TRAEs) than those in the combination group (n = 22, 62.9%). There were also fewer patients with TRAEs of grades 3–5 with monotherapy (n = 2, 10.5%) than with combination therapy (n = 7, 20.0%). Pneumonitis in three patients was the only potential immune-related adverse event reported. Conclusions Anti-PD-1-based monotherapy and combination therapy showed favorable survival outcomes and manageable safety profiles in advanced or metastatic GC/GEJCs. In clinical treatment, immunotherapy should be an indispensable choice in the treatment strategy for GC/GEJC. Patients with a heavy tumor burden and more metastatic sites might benefit more from combination therapy. Elderly patients and patients with more treatment lines or high Eastern Cooperative Oncology Group (ECOG) performance scores might be more suitable for immune monotherapy, and some clinical benefits have been observed.